2021
DOI: 10.1523/eneuro.0114-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Neuromarkers from Whole-Brain Functional Connectivity Reveal the Cognitive Recovery Scheme for Overt Hepatic Encephalopathy after Liver Transplantation

Abstract: Neuromarkers from whole-brain functional connectivity reveal the cognitive recovery scheme for overt hepatic encephalopathy after liver transplantation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Other studies identified factors associated with cognitive function after LT but did not specifically provide data on how these factors modify the risk of cognitive impairment after LT. These factors included MHE, 5 OHE, 3 , 9 , 28 30 , 38 40 alcohol-associated cirrhosis, 26 , 40 immunosuppression, 9 , 40 diabetes, 40 and MELD score. 3 A novel factor associated with post-LT cognitive function that was elucidated from the included studies was that of gut dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies identified factors associated with cognitive function after LT but did not specifically provide data on how these factors modify the risk of cognitive impairment after LT. These factors included MHE, 5 OHE, 3 , 9 , 28 30 , 38 40 alcohol-associated cirrhosis, 26 , 40 immunosuppression, 9 , 40 diabetes, 40 and MELD score. 3 A novel factor associated with post-LT cognitive function that was elucidated from the included studies was that of gut dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 24 included studies, 23 (96%) were prospective cohort studies with duration of follow-up ranging from 1 mo to 1.8 y after LT. 1,2,5,[7][8][9][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The median number of patients in the included studies was 30 (interquartile range: 21.5-50.5). Ten (42%) studies were conducted in Europe, 2,9,26,[33][34][35][36][40][41][42] 9 (38%) in Asia, 8,[27][28][29][30][31][32]38,39 and 5 (21%) in the United States. 1,3,5,7,37 Twenty-three studies (96%) reported the mean or median age, which was between 31 and 65 y.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, CPM discovers meaningful patterns by using simple linear regression models. Because of this approach, it is especially helpful for psychologists, neuroscientists, and clinicians ( Cheng et al, 2021 ) who may have limited background knowledge of more complicated quantitative approaches such as multi-variant pattern analysis (MVPA) and machine learning techniques.…”
Section: Connectome-based Predictive Modelingmentioning
confidence: 99%